Formulation and stabilization of protein-loaded nanoparticles and potential therapeutic applications thereof - Alam, K M Khairul (2017)
Myocardial infarction is a medical emergency and needs an immediate treatment with reperfusion therapy. But, reperfusion itself causes damage to the myocardium by overproduction of reactive oxygen species (ROS). These excessive ROS generated during reperfusion lead to oxidative stress in the myocardium and damage to the cardiomyocytes. Reperfusion injury has been suggested to be responsible for up to 50% of the final infarct size of the myocardium and this resultant infarct size is highly related with the development of chronic heart failure. Although both the superoxide anion and hydrogen peroxide are elevated following myocardial infarction, the levels of their endogenous scavenger enzymes, superoxide dismutase and catalase, decrease even more. Catalase is a major antioxidant enzyme in the body’s endogenous antioxidant defence systems and this enzyme is considered to be responsible for most of the peroxidase activities in the cardiomyocytes. Delivery of active proteins such as catalase to the myocardium is challenging as they can easily be inactivated by proteases, aggregation and natural inhibitors. Delivery of therapeutic proteins using polymeric nanoparticles can offer an attractive approach. No studies on evaluation of the cardio-protective effect of catalase-loaded nanoparticles in conserving cardiomyocytes from the oxidative stress induced by reperfusion injury have been reported yet. Poly(lactic-co-glycolic acid) (PLGA) is a US Food & Drug Administration (US FDA)-approved biocompatible and biodegradable polymer, and this polymer was used in this study to prepare catalase-loaded nanoparticles. In the double emulsion method of fabricating protein-loaded nanoparticles, emulsification process induces denaturation of proteins. No reports have showed the effects of trehalose and bovine serum albumin on the encapsulation of catalase into PLGA nanoparticles and comparison of their effects yet. This study showed that trehalose and bovine serum albumin added to the initial aqueous phase as a stabilizer of the catalase activity were observed to be effective in reducing loss of enzymatic activity of catalase during emulsification steps of the enzyme encapsulation process in the double emulsion method. Surprisingly, unlike BSA-stabilized catalase-loaded PLGA nanoparticles, trehalose-stabilized nanoparticles showed very low enzymatic activity which was comparable to the catalase activity of the unstabilized nanoparticles. Freeze-drying is a useful technique to stabilize the nanoparticles and proteins. But, the process of freeze-drying itself exerts stresses resulting in aggregation of the nanoparticles and denaturation of the proteins. Cryoprotectants are added to protect the nanoparticulate systems from the damage induced by the freeze-drying process. Trehalose is a well-known cryoprotectant. No studies on the cryoprotective effect of trehalose in reducing the loss of enzymatic activity of the encapsulated catalase upon freeze-drying of the catalase-loaded PLGA nanoparticles have been reported yet. In this study, trehalose added as a cryoprotectant minimized the loss of enzymatic activity of the encapsulated catalase of catalase-loaded nanoparticles in a dose-dependent manner. Cryoprotected catalase-loaded nanoparticles were found to be effective in reducing oxidative stress-induced damage in a widely recognized hydrogen peroxide-induced cellular model of oxidative stress in HL-1 cardiomyocytes. This protective response was dose-dependent. The nanoparticles also demonstrated efficacy in reducing apoptosis that plays an important role in myocardial cell death during reperfusion of the myocardium and is linked with the development of heart failure following myocardial infarction. Structural study of the encapsulated catalase of catalase-loaded nanoparticles was performed by Attenuated Total Reflectance-Fourier Transform Infrared (ATR-FTIR) spectroscopy and fluorescence spectroscopy which showed that trehalose could reduce the encapsulated enzyme’s structural alterations induced by freeze-drying of the nanoparticles. The promising cardioprotective effect demonstrated by the cryoprotected catalase-loaded PLGA nanoparticles in rescuing cardiomyocytes from oxidative stress, makes this catalase-loaded nanoparticle a valuable candidate for the treatment of reperfusion injury and warrants further investigation including animal trials.